The detection of types among decathletes using Configural Frequency Analysis (CFA) - Stemmler, M.; Bäumler, G. (Psychology Science, 2005)
The aim of this exploratory study was to detect among decathletes types of specialization with the help of a one sample configural frequency analysis (CFA). The sample consisted of the performances of 514 decathlon athletes, who were ranked among the top 100 athletes of the world from 1984 to 2000. Due to the fact that some athletes were ranked repeatedly among the top 100 world`s best athletes, each athlete was listed only once with his best performance. Due to sample size constraints only six out of the ten events were entered into a CFA. Therefore, a total of five CFAs with different combinations of events were conducted. The analysed sets of events were derived from factor analyses which were performed in advance. The resulting number of types varied between one and five. The resulting types could be labelled either `allround-types` who were proficient in three out of four or in all four factors of performances (i.e., sprinting, throwing, jumping and stamina) or`specialist-types` who were proficient in only two factors or two events (e. g., factors throwing and stamina; events javelin throw and 1500m run or shot put and discus throw or 100m run and 1500m run). In two cases `solitary-types` evolved with excellent performances in shot put or 1500m run. The 1500m run was part of most types detected. The results suggested that there exist meaningful decathlon types who can be detected with CFA.